BOLD magnetic resonance imaging of skeletal muscle. - Noseworthy, MD; Bulte, D; Alfonsi, J (2003)
Blood-oxygen-level-dependent (BOLD) imaging was a concept introduced in 1990 for evaluating brain activation. The method relies on magnetic resonance imaging (MRI) contrast resulting from changes in the microvascular ratio of oxyhaemoglobin (oxyHb) to deoxyhaemoglobin (deoxyHb). OxyHb is diamagnetic, whereas deoxyHb is paramagnetic, which produces a local bulk magnetic susceptibility effect and subsequent MRI signal change. The changes are typically observed in T(2)*-weighted functional MRI scans. However, there has recently been interest in BOLD as a way to evaluate microcirculation of any normal or diseased tissue. This review focuses on the application of BOLD imaging in the understanding of normal and diseased skeletal muscle. In addition we present new findings showing the possible application of BOLD imaging with hyperoxia for evaluating skeletal muscle physiology.